Influence of stone load on the outcome of same-session flexible ureteroscopy for bilateral upper urinary tract stones: a multicenter retrospective study - Tu, Wei-Chao; Zhang, Xin-Le; Wang, Jun; Huang, Bao-Xing; Zhang, Ding-Guo; Wang, Da-Wei (Frontiers in Medicine, 2023)
Purpose: To evaluate the efficacy and safety of same-session flexible ureteroscopy(fURS) for treatment of bilateral upper urinary tract stones and stratify the influence of stone loads on the outcome of same-session fURS by total diameter of stones (TDS) ≤30 mm and >30 mm. Patients and Methods: We retrospectively reviewed all cases of same-session fURS performed for bilateral upper urinary tract stones at four institutions between January 2017 and September 2020. All patients were divided into two groups based on TDS≤30 mm and >30 mm. Patient demographics, stone characteristics, surgical results, and complications were collected and analysed between the two groups. Stone free rate(SFR) was defined as endoscopically stone-free or radiological fragments <2 mm of each renal unit. Results: A total of 121 bilateral upper urinary tract stones patients underwent same-session fURS, including 73 patients in TDS ≤ 30 mm group and 48 patients in TDS >30 mm group. The mean bilateral stone size was 28.2 ± 12.2 mm (range: 9.1-38.4 mm) with a mean operating time of 97.1 ± 39.6 minutes (range 19-220 minutes). SFR was 54.5% after the first fURS and SFR rose to 97.5% after re-fURS for residual stones. The operation time of TDS >30mm group was longer than that of TDS ≤ 30mm group (85.1± 36.5 vs 115.4± 37.4 min, p<0.001). The SFR in TDS >30mm group was significantly lower than that in TDS ≤30mm group after the first fURS ( 25.0% vs 73.9%, p<0.001). Although there was no statistical difference in overall SFR between the two groups(93.7% vs 100%, p=0.060), the rate of re-fURS for residual stones in TDS >30mm group is higher than that in TDS≤30mm group( 75% vs 26%, p<0.001 ). There were no significant differences in length of hospital stay(LOS) (2.2 ± 0.7 vs 2.3 ± 1.0, p=0.329) and complication rate(10.9% vs 14.6%, p=0.582) between the two groups. Conclusions: The results suggested that same-session fURS can be effectively performed with low complication rate. Bilateral upper urinary tract stones with TDS≤30 mm can achieved a higher SFR after the first fURS and priority should be given to same-session fURS.